Large Extent Volunteer Roadkill and Wildlife Observation Systems as Sources of Reliable Data - Waetjen, David P.; Shilling, Fraser M. (Frontiers in Ecology and Evolution, 2017)
Large-extent wildlife-reporting systems have sets of goals and methods to facilitate standardized data collection, statistical analysis, informative visualizations, and use in decision-making within the system area. Many systems employ “crowds” of volunteers to collect these data at large spatial extents (e.g., US state or small country scale), especially along roadways. This raises the important question of how these systems could be standardized and the data made broadly useful in ecological and transportation studies, i.e. beyond the system area or goals. We describe two of the first and longest-running systems for volunteer observation of road-associated wildlife (live and dead) at the US state scale. The California Roadkill Observation System (CROS, http://wildlifecrossing.net/california) uses a form-based data entry system to report carcasses resulting from wildlife-vehicle collisions (WVC). Operating since 2009, it currently (June, 2017) contains 1,338 users and >54,000 observations of 424 species of ground-dwelling vertebrates and birds, making it one of the most successful examples of crowd-sourced, roadkill and wildlife reporting. Its sister system, the Maine Audubon Wildlife Road Watch (http://wildlifecrossing.net/maine) has a similar structure, and can accept data from transect surveys, animal tracks and scat observations, and reports of “no animal observed”. Both systems can operate as web-applications on a smart-phone (using a web browser), providing the ability to enter observations in the field. Locational accuracy for California observations was estimated to be +/-14 m (n=552 records). Species identification accuracy rate for observations with photographs was 97% (n=3,700 records). We propose that large extent, volunteer systems can be used to monitor wildlife occurrences along or away from roads and that these observations can be used to inform ecological studies and transportation mitigation planning.